Histopathological Study of Full-Term Placenta in Selected Normotensive And Pre-eclamptic Women in Bangladesh - Khan, Nahid Ahmed; Nahid, Nuzaira; Chowdhury, Malia; Hossain, Mohammad Zaid; Patwary, Mohammad Shamsul Arefin; Kamal, Mohammad Mostafa; Ikra, Khandaker Farah Anjuman (Journal of Dhaka Medical College, 2023)
Pre-eclampsia is a disorder of 2nd half of pregnancy, which is characterized by a combination of hypertension, proteinuria and edema, secondary to decreased placental perfusion. Clinical studies suggest that there are histopathological changes in the placenta of pre-eclamptic women, compared to normotensive pregnant women. In developing countries, pre-eclampsia causes an estimated 50,000 maternal deaths per year. Only a small number of studies have however, been conducted in Bangladesh. Objective: To compare the histopathology of placenta in selected pre-eclamptic and normotensive pregnant women. Methods: 220 pregnant women were selected with inclusion and exclusion criteria from 3 different medical colleges and divided into 2 groups – A study group, consisting of 110 pre-eclamptic women and a control group consisting of 110 normotensive pregnant women. Dietary information was collected by 7 days food frequency questionnaire and food score was determined. Anthropometric and biochemical tests were performed. To evaluate the histopathology of placenta, tissue samples were collected from the placenta after delivery, and were prepared for histopathological studies, by haemotoxylin and eosin stain method. The mean number of areas of syncytial knot formation, the mean number of areas of cytotrophoblastic cell proliferation, the mean number of areas of fibrinoid necrosis, and the mean number of areas of hyalinised villi of pre-eclamptic and normal pregnant women were evaluated. Results: The mean number of areas of syncytial knot formation, the mean number of areas of cytotrophoblastic cell proliferation, the mean number of areas of fibrinoid necrosis, and the mean number of areas of hyalinised villi were found to be significantly higher in the study group, compared to the control group. Conclusion: Therefore, mean number of areas of syncytial knot formation, the mean number of areas of cytotrophoblastic cell proliferation, the mean number of areas of fibrinoid necrosis is increased in the placenta of pre-eclamptic women, compared to normotensive pregnant women. J Dhaka Med Coll. 2021; 30(2) : 189-195